Immune Tolerance to Apoptotic Self Is Mediated Primarily by Regulatory B1a Cells - Miles, Katherine; Simpson, Joanne; Brown, Sheila; Cowan, Graeme; Gray, David; Gray, Mohini (Frontiers in Immunology, 2018)
The chronic autoimmune inflammatory diseases, systemic lupus erythematosus (SLE) and Sjogren’s syndrome, develop when tolerance to apoptotic cells is lost. We have previously reported that this tolerance is maintained by innate-like, IL-10 secreting regulatory B cells. Two questions remained. First, do these regulatory B cells belong pre-dominantly to a single subset of steady-state B cells and second, what is their specificity? We report here that innate-like B cells with markers characteristic for B1a cells (CD43+veCD19hiCD5+veIgMhiIgDlo) constitute 80% of splenic and 96% of peritoneal B cells that respond to apoptotic cells by secreting IL-10. Apoptotic cell responsive B1a cells secrete self-reactive natural antibodies and IL-10, which is augmented by toll like receptor (TLR) 7 or TLR9 stimulation. In so doing, they both accelerate the clearance of dying cells by macrophages and inhibit their potential to mount pro-inflammatory immune responses. Whilst B1a cells make prolonged contact with apoptotic cells, they do not require TIM1 or complement to mediate their regulatory function. In an animal model of neural inflammation, (experimental autoimmune encephalomyelitis), just 105 activated B1a B cells was sufficient to restrain inflammation. Activated B1a B cells also induced antigen specific T cells to secrete IL-10. Hence regulatory B1a cells specifically recognize and augment tolerance to apoptotic self via IL-10 and natural antibodies; but once activated, can also prevent autoimmune mediated inflammation.